Exploring the handedness-breast cancer nexus: a comprehensive analysis via systematic review, meta-analysis, and Mendelian randomization - Chi Young Oh; Eugene Kim; Kihun Kim; Hyeoncheol Oh; Jung-Pil Yoon; Tae Sik Goh; Eunjeong Son; Dai Sik Ko; Yun Hak Kim (Therapeutic Advances in Medical Oncology, 2024)
Background: Given the widespread prevalence of breast cancer as a global malignancy, there is a compelling need to delve into its risk determinants. Objective: This study aims to investigate the potential relationship between indicators of left-handedness and breast cancer, employing systematic review, meta-analysis, and Mendelian randomization methods. Design: Systematic review and meta-analysis. Methods: The systematic review and meta-analysis, encompassing case-control and cohort designs, conducted a database search on June 17, 2022, utilizing Medline and Embase. For Mendelian randomization analysis, the exposure variable, left-handedness, was sourced from the UK Biobank. Data for breast cancer outcomes were obtained from two cohorts: the Breast Cancer Association Consortium and the Finnish Biobank (Finngen). Results: Eight studies were included in the meta-analysis to investigate the correlation between left-handedness and breast cancer in females. The analysis of cohort studies revealed a hazard ratio (HR) of 1.21 (95% confidence interval (CI): 1.01–1.45), whereas case-control studies showed an odds ratio of 0.81 (95% CI: 0.52–1.26). Subgroup analysis indicated an elevated HR in premenopausal left-handed women. However, Mendelian randomization did not confirm a significant association. Conclusion: Our findings suggest a potential correlation between left-handedness and breast cancer, particularly in premenopausal women. However, due to limited studies and unclear supporting theories, definitive conclusions are premature.